When Do Enterprises Prefer Informal Credit? - Safavian, Mehnaz (The World Bank, 2008)
This paper tests the hypothesis that enterprises may forgo formal finance in lieu of informal credit by choice. They do so to avoid the additional regulatory scrutiny and harassment that engaging with the formal financial sector invites. We test this hypothesis using enterprise-level data on 3,564 enterprises in 29 countries. In this sample, enterprises finance approximately 57 percent of their working capital requirements with external finance. This external finance comes from formal sources, such as commercial banks (53 percent) and informal sources (42 percent), such as trade creditors, or family and friends. In our sample, 14 percent of enterprises rely exclusively on informal finance. We find that the likelihood of enterprises preferring to only use informal finance is inversely related to the quality of the regulatory environment, particularly the quality of tax administration and overall governance. For example, we find that when an enterprise has been asked for bribes by tax inspectors, it is 17 percent more likely to prefer informal finance